Enantioselective total synthesis of (−)-Himalensine A via a palladium and 4-hydroxyproline co-catalyzed desymmetrization of vinyl-bromide-tethered cyclohexanones - Kučera, R; Ellis, SR; Yamazaki, K; Hayward Cooke, J; Chekshin, N; Christensen, KE; Hamlin, TA; Dixon, DJ (American Chemical Society, 2023)
Herein, we describe the convergent enantioselective total synthesis of himalensine A in 18 steps, enabled by a highly enantio- and diastereoselective construction of the morphan core via a palladium/hydroxy proline co-catalyzed desymmetrization of vinyl-bromide-tethered cyclohexanones. The reaction pathway was illuminated by density functional theory calculations, which support an intramolecular Heck reaction of an in situ-generated enamine intermediate, where exquisite enantioselectivity arises from intramolecular carboxylate coordination to the vinyl palladium species in the rate- and enantio-determining carbopalladation steps. The reaction tolerates diverse N-derivatives, all-carbon quaternary centers, and trisubstituted olefins, providing access to molecular scaffolds found in a range of complex natural products. Following large-scale preparation of a key substrate and installation of a β-substituted enone moiety, the rapid construction of himalensine A was achieved using a highly convergent strategy based on an amide coupling/Michael addition/allylation/ring-closing metathesis sequence which allowed the introduction of three of the five rings in only three synthetic steps (after telescoping). Moreover, our strategy provides a new enantioselective access to a known tetracyclic late-stage intermediate that has been used previously in the synthesis of many Daphniphyllum alkaloids.